Tuning the Lewis acid phenol ortho-prenylation as a molecular diversity tool - Jäger, Sebastian Nicolas (2016)
A diversity-oriented approach for the synthesis of various structurally different prenylated alcohols from readily accessible and common precursors was developed. With varying approaches, this article describes some successful examples of a Friedel–Crafts alkylation using methoxyphenols and different prenyl alcohols (geraniol and (E,E)-farnesol). We demonstrated that just by varying the stoichiometry of the Lewis acid used, the course of the reaction can be shifted to produce the alkylated or the cyclized product. Eighteen unique products were obtained with good isolated yields by direct alkylation with or without a consecutive (Formula presented.) -cationic cyclization.